Long-term trends in first arrival and first egg laying dates of some migrant and resident bird species in northern Italy - Rubolini, D; Caffi, M; Brichetti, P; Armiraglio, S; Saino, N.; AMBROSINI, ROBERTO (International Journal of Biometeorology, 2007)
Climate change is affecting the phenology of seasonal events in Europe and the Northern Hemisphere, as shown by several studies of birds¿ timing of migration and reproduction. Here, we analyse the long-term (1982¿2006) trends of first arrival dates of four long-distance migratory birds [swift (Apus apus), nightingale (Luscinia megarhynchos), barn swallow (Hirundo rustica), and house martin (Delichon urbicum)] and first egg laying dates of two migrant (swift, barn swallow) and two resident species [starling (Sturnus vulgaris), Italian sparrow (Passer italiae)] at a study site in northern Italy. We also addressed the effects of local weather (temperature and precipitation) and a climate index (the North Atlantic Oscillation, NAO) on the interannual variability of phenological events. We found that the swift and the barn swallow significantly advanced both arrival and laying dates, whereas all other species did not show any significant temporal trend in either arrival or laying date. The earlier arrival of swifts was explained by increasing local temperatures in April, whereas this was not the case for arrival dates of swallows and first egg laying dates of both species. In addition, arrival dates of house martins were earlier following high NAO winters, while nightingale arrival was earlier when local spring rainfall was greater. Finally, Italian sparrow onset of reproduction was anticipated by greater spring rainfall, but delayed by high spring NAO anomalies, and swift¿s onset of reproduction was anticipated by abundant rainfall prior to reproduction. There were no significant temporal trends in the interval between onset of laying and arrival in either the swift or the barn swallow. Our findings therefore indicate that birds may show idiosyncratic responses to climate variability at different spatial scales, though some species may be adjusting their calendar to rapidly changing climatic conditions.